The Effectiveness of Health Screening - Franz Hackl; Martin Halla; Michael Hummer; Gerald J. Pruckner (Johannes Kepler University of Linz, Department of Economics, 2012)
Using a matched insurant-general practitioner panel data set, we estimated the effect of a general health-screening program on individuals health status and health care cost. To account for selection into treatment, we used regional variations in the intensity of exposure to supply-determined screening recommendations as an instrumental variable. We found that screening participation substantially increased inpatient and outpatient health care costs for up to two years after treatment. In the medium term, we found cost savings in the outpatient sector, whereas in the long run, no statistically significant effects of screening on either health care cost component could be discerned. In summary, screening participation increases health care costs. Since we did not find any statistically significant effect of screening participation on insurants health status at any point in time, we do not recommend a general health-screening program. However, given that we found some evidence for cost-saving potentials for the sub-sample of younger insurants, we suggest more targeted screening programs.
Keywords: I10; I18; 330; Health screening; health care costs; sick leave; mortality; Gesundheitsvorsorge; Wirkungsanalyse; Gesundheit; Gesundheitskosten; Erwerbsunfähigkeit; Schätzung; Österreich